Reduction of Pain and Bacterial Presence by using Double and Triple Antibiotic Pastes in Symptomatic Apical Periodontitis - Dall, Abdul Qadir Khan; Tasleem, Farah; Khan, Muhammad Farhan; Channar, Kashif Ali; Batool, Sarwat; Bari, Muhammad Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To compare the efficacy of calcium hydroxide, triple antibiotic paste and double antibiotic paste in reducing bacterial load and post treatment pain in symptomatic apical periodontitis. METHODOLOGY: In this comparative cross sectional study, 30 patients were divided into three groups. After sample collection Group A (control group) was medicated with calcium hydroxide (CH) paste, Group B with triple antibiotic paste (TAP) and Group C with double antibiotic paste (DAP). On day seven, pain status was checked by using visual analogue scale and canals were washed and another bacterial sample was taken and sent to laboratory to evaluate bacterial count. Evaluation of bacterial count and pain was done. Data analysis was performed in statistical packages for social sciences (SPSS) version 20.0. Mean & SD was calculated. Paired T-test was applied to compare qualitative data of control group with other two groups and P value (< 0.05) perceived as significant. RESULTS: All baseline samples were positive for bacteria with considerable pain. Following 07 days post-treatment VAS (visual analogue scale) showed mean value of 2.5±1.269 for CH, 1.7±0.823 for TAP and 2.0±1.054 for DAP. In post-treatment presence of Bacteria, mean was 1.1±0.316 for CH, 1.3±0.483 for TAP and 1.2±0.422 hence post treatment bacteria presence was lower in TAP and DAP and was higher in CH group. CONCLUSION: From the results it is concluded that DAP provided better antimicrobial effect with significant decrease in pain and bacterial count in comparison to control group and almost equal in efficacy to TAP.